Impacts of Neanderthal-Introgressed Sequences on the Landscape of Human Gene Expression - McCoy, Rajiv C.; Wakefield, Jon; Akey, Joshua M. (Cell, 2017)
Regulatory variation influencing gene expression is a key contributor to phenotypic diversity, both within and between species. Unfortunately, RNA degrades too rapidly to be recovered from fossil remains, limiting functional genomic insights about our extinct hominin relatives. Many Neanderthal sequences survive in modern humans due to ancient hybridization, providing an opportunity to assess their contributions to transcriptional variation and to test hypotheses about regulatory evolution. We developed a flexible Bayesian statistical approach to quantify allele-specific expression (ASE) in complex RNA-seq datasets. We identified widespread expression differences between Neanderthal and modern human alleles, indicating pervasive cis-regulatory impacts of introgression. Brain regions and testes exhibited significant downregulation of Neanderthal alleles relative to other tissues, consistent with natural selection influencing the tissue-specific regulatory landscape. Our study demonstrates that Neanderthal-inherited sequences are not silent remnants of ancient interbreeding but have measurable impacts on gene expression that contribute to variation in modern human phenotypes. [Display omitted] •We devised a flexible method to quantify allele-specific expression across samples•One-quarter of Neanderthal-introgressed haplotypes show cis-regulatory effects•Introgressed regulatory variants add to genomic complexity and phenotypic diversity•Neanderthal alleles are downregulated in genes expressed in the brain and testes Genome-wide interrogation of the functional differences between modern human and Neanderthal alleles reveals that Neanderthal-inherited sequences are not silent remnants of ancient interbreeding but have a measurable impact on gene expression that may contribute to phenotypic variation in modern humans.